Prevalence of large vessel occlusions in an unselected hospital-based stroke cohort in Sweden - Roland, Mihae; Markaki, Ioanna; Arnberg, Fabian; Klironomos, Stefanos; Sjöstrand, Christina (Frontiers in Neurology, 2025)
IntroductionDetermining the prevalence of large vessel occlusions (LVOs) is important for planning and accessing mechanical thrombectomy treatment. Previous estimates vary greatly in studies, which might be related to different inclusion criteria and/or selection bias. In this cohort study, we aimed to determine the presence of LVO in an unselected, i.e., untriaged, hospital-based stroke cohort in Sweden.MethodsStroke patients treated at Karolinska Huddinge University Hospital were consecutively collected during the years 2008 through 2015, identified by an ICD-10 diagnosis of ischemic stroke (I63). Patients with LVO were selected through radiology reports indicating LVO.ResultsA total of 3,152 consecutive patient events had received a diagnosis of ischemic stroke during the study period. A total of 356 occlusion events were found in the internal carotid artery, the first two segments of the middle cerebral artery (M1, M2), and anterior cerebral artery (A1, A2), the vertebral artery, basilar artery and the first two segments of the posterior cerebral artery (P1, P2). This resulted in an LVO prevalence of 11.3% in this cohort. Seventy-six percent of occlusions were located in the anterior circulation, and 24% in the posterior circulation. The most frequent occluded vessel was M1 (n = 166, 39%).ConclusionIn this study of consecutively collected stroke patients the prevalence of LVO was lower compared to other studies, possibly related to our unselected patient cohort, limited use of CT angiography, and/or the LVO definition used. These results are of importance for decision-making regarding the capacity of comprehensive stroke centers.